Microwave, Radar & RF Engineering With Laboratory Manual - Chaturvedi, Prakash Kumar; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This is a textbook for upper undergraduate and graduate courses on microwave engineering, written in a student-friendly manner with many diagrams and illustrations. It works towards developing a foundation for further study and research in the field. The book begins with a brief history of microwaves and introduction to core concepts of EM waves and wave guides. It covers equipment and concepts involved in the study and measurement of microwaves. The book also discuses microwave propagation in space, microwave antennae, and all aspects of RADAR. The book provides core pedagogy with chapter objectives, summaries, solved examples, and end-of-chapter exercises. The book also includes a bonus chapter which serves as a lab manual with 15 simple experiments detailed with proper circuits, precautions, sample readings, and quiz/viva questions for each experiment. This book will be useful to instructors and students alike. .
Introduction to Microwaves -- Transmission Lines, Waveguides, Strip Lines and Stub Matching by Smith Chart -- Microwaves Cavity Resonators -- Microwaves Components and their Scattering Matrices -- Microwave Tubes as Microwave Source (Oscillators) and Amplifiers -- Microwave Semiconductors Devices: Oscillators, Amplifiers and Circuit -- Microwave Measurement: Instruments and Techniques -- Microwaves Propagation in Space and Microwave Antennas -- Radar -- RF Filter Design -- RF Amplifiers, Oscillator and Mixers -- Simple Lab Experiments and Lab Manual.
Keywords: Telecommunication; Electronic circuits; Lasers; Microwaves, RF Engineering and Optical Communications; Electronic Circuits and Systems; Laser